Effects of nano-zerovalent iron on antibiotic resistance genes and mobile genetic elements during swine manure composting. (March 2020) - Wang, Qianzhi; Gu, Jie; Wang, Xiaojuan; Ma, Jiyue; Hu, Ting; Peng, Huiling; Bao, Jianfeng; Zhang, Ranran
Absract: Livestock manure is a reservoir for antibiotic resistance genes (ARGs), and aerobic composting is used widely for recycling animal manure. This study investigated the effects of adding nano-zerovalent iron (nZVI) at 0, 100, and 1000 mg/kg on the fates of ARGs and mobile genetic elements (MGEs) during swine manure composting. Under nZVI at 100 mg/kg, the relative abundances of sul1, sul2, dfrA7, ermF, and ermX decreased by 33.26–99.31% after composting, and the relative abundances of intI2 and Tn916/1545 decreased by 95.59% and 97.65%, respectively. Most of the ARGs and MGEs co-occurred and they had strong correlations with each other. The bacterial community structure was significantly separated by the composting periods, and they clustered together under different treatments in the same phase. Network analysis showed that Solibacillus, Clostridium_sensu_stricto_1, Terrisporobacter, Rombou t s ia, Turicibacter, Lactobacillus, Planococcus, Dietzia, and Corynebacterium_1 were common potential hosts of ARGs and MGEs. Redundancy analysis suggested that MGEs had key effects on the variations in the relative abundances of ARGs. Adding 100 mg/kg nZVI could reduce the environmental risk of ARGs by decreasing the abundances of MGEs. Graphical abstract: Image 1 Highlights: Adding 100 mg/kg nZVI most effective at removing ARGs and MGEs. Most of the ARGs and MGEs co-occurred and they were highly correlated. Seventeen genera identified as potential host bacteria for ARGs and MGEs. MGEs responsible for variations in the ARG profiles. Abstract : Adding 100 mg/kg nZVI led to lower relative abundances of 6/12 ARGs and MGEs were responsible for the changes in ARGs.